MicroRNAs in prion diseases - Zimbardi, Daniela [UNESP]; Pereira, Tiago Campos (My University, 2016)
MicroRNAs (miRNAs) encompass a class of small RNA molecules (18-22 nucleotides) able to regulate gene expression posttranscriptionally, controlling virtually all processes in the cell in an unforeseen new manner. On the other hand, prions are unique pathogens composed solely of proteins and cause a class of intriguing fatal neurodegenerative diseases, such as bovine spongiform encephalopathy (also known as mad cow disease) and Creutzfeldt-Jakob disease in humans, among many others. Recently, a series of reports has revealed unexpected and curious associations between prions and miRNAs. This chapter discusses on them, as follows: (i) the concept of prion as an infectious agent, (ii) miRNA signature in the preclinical and clinical stages of prion diseases, (iii) occurrence of pathogenic prions and miRNAs in exosomes, (iv) prion interactions with miRNA machinery, (v) use of artificial miRNAs to knockdown prions, and (vi) prion-like domains of miRNA-binding proteins. This chapter provides an unparalleled connection between two of the most fascinating concepts in modern molecular biology: prions and miRNAs, both of which have considerably changed our understanding of the cell. Investigations on the crosstalk between these two fields started only very recently, thus representing a new, exciting, and very promising research area.